Socio-economic Determinants of Health Expenditure for Low-income Householdsin the Informal Sector - M Kazemiyan; H Javadi-Nasab (Journal of Kerman University of Medical Sciences, 2014)
Background & Aims: People`s health, life expectancy and quality of life have been affected by social determinants of health, significantly. Also, socio-economic factors may affect health expenditure, considerably. This study has evaluated the effects of socio-economic determinants on health expenditure for the low-income urban householdsin the informalsector of employment. Methods: In this study, the socio-economic data for the low-income urban households in the informal sector were obtained from the results of households’ budget survey from the Statistical Center and the Central Bank of Iran, for the years 1986-2009. This was the first study used the record data for contingent valuation method. The ordinary leastsquaresregression model was used for data analysis. Results: Increase in age, education level, income and family size increased health expenditure of the householdsin the informal sector; and increase in urban unemployment rate decreased health expenditure of the households. Besides, the mean age of the young years and the unemployment rate had the highest and lowest effects on households` health expenditure, respectively. Conclusion: In the two last decades, changes in the demand of low income households for health services mainly arise from changes in the socio-economic determinants of consumers’ behavior. Social health insurance is a suitable mechanism for financing health expenditure of the low income households. Arbitrary health insurance plan in the informal sector, existence of some rules and regulations, and inappropriate premiums with respect to the minimum wage make the universal coverage of social health insurance for this group of population problematic.